Canadian public finance - Strick, J. C. (Toronto : Holt, Rinehart and Winston of Canada, 1973)
This book concentrates on government financial institutions and practices and problems of government finance in Canada, and describes and analyses government policies, with emphasis on the federal level of government.
Distributed in the U.S.A. by Winston Press, Minneapolis.
Includes bibliographical references and index.
sju 22/01/2019
Loan
Keywords: Finance, Public